Beyond Numbers: Realistic Mathematics Education in Mathematics in Action to Enhance Students' Problem-Solving Skills - Mazlan Mazlan; Wahyuni Wahyuni; Rosmiati Rosmiati (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2025)
This research aims to improve the mathematical problem-solving abilities of class XII Langsa State High School students through the application of the Principles of Realistic Mathematics (PMR). The research method used is Classroom Action Research (PTK) with three cycles. The research subjects were 28 students. Data was obtained through problem-solving ability tests, observation of teacher activities, and student activities in learning. The research results show that the application of PMR is effective in improving students' problem-solving abilities. In cycle I, the students' average score reached 65.43 with classical completeness of 53.57%. This value increased to 72.86 in cycle II with classical completeness of 75.00%, and in cycle III it increased again to 80.23 with classical completeness of 89.28%. Apart from that, teacher activity in learning with PMR also increased from cycle to cycle, with the average value of teachers' ability to manage learning increasing from 3.00 in cycle I, to 3.25 in cycle II, and 3.45 in cycle III. Student learning activities also show an increase. In cycle I, the percentage of student activity was 62.50% (sufficient category), increased to 70.83% in cycle II (good category), and reached 78.57% in cycle III (active category). Students are more active in understanding contextual problems, discussing to find solutions, and summarising learning results. With these results, it can be concluded that the PMR approach can improve students' mathematical problem solving, student learning activities, and the effectiveness of teacher learning management. Therefore, PMR is recommended as a learning strategy that can be applied in mathematics learning at the high school level.